Great classic women's fiction [compact disc, unabridged] : ten unabridged stories - Cather, Willa, 1873-1947; Cather, Willa, 1873-1947; Chopin, Kate, 1850-1904; Chopin, Kate, 1850-1904; Chopin, Kate, 1850-1904; Chopin, Kate, 1850-1904; Gilman, Charlotte Perkins, 1860-1935; Gilman, Charlotte Perkins, 1860-1935; Wharton, Edith, 1862-1937; Wharton, Edith, 1862-1937; McGlasson, Chris; Walters, Tamara; et al. (AudioGO, 2011)
Enduring stories that are as relevant today as they were when written at the turn of the century by influential women writers.